Attitudes of students of the Faculty of Education about pedagogical practice in their preparation for service (Práxis Educativa, 2024)
This research has the pedagogical practice of the Faculty of Education as an object of study, with a special emphasis on presenting the attitudes of students before the service for the pedagogical practice in the study program Preschool Education and Primary Education. Since the scope of these programs within the Faculties of Education has the mission of teaching, then we are oriented to do this study with the qualitative research method through a semi-structured interview with a total of 15 students of these programs for pedagogical practice.Using the literature and official documents of the Faculty of Education, such as the study program and the practical teaching manual, we came to the arguments that Pedagogical Practice during the four-year studies divided into each year of studies is necessary and a prerequisite for a future in the process educational and training of intern students.This research is quite important, because it serves students of the Faculties of Education, teachers, professors of higher education, and as such is useful for the sciences of Education in general.The researches show that students during the process of practical learning, in addition to the advantages, also have difficulties and shortcomings that follow this process.